Extensive Epidermoid Cyst and Breathing Difficulty - Ciro Dantas Soares; Alberto Costa Gurgel; Francisco de Assis de Souza Júnior; Samila Neres de Oliveira; Maria Goretti Freire de Carvalho; Hanieri Gustavo Oliveira (Case Reports in Dentistry)
Epidermoid cysts are common cystic lesions in the skin, ovaries, and testicles, but their occurrence in the oral cavity is uncommon. They consist of cysts delimited by a fibrous capsule without cutaneous annexes and are lined by stratified squamous epithelium. The differential diagnosis includes ranula, dermoid cysts, and lingual thyroid. Despite their benign presentation, these cysts can cause functional limitations, requiring special clinical attention for extensive lesions located in regions that preserve vital structures. This paper aims to report a case of epidermoid cyst in patient with swallowing and breathing difficulty, highlighting the clinical and surgical planning.